Pengaruh Budaya Organisasi, Kompensasi Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada BMT Surya Abadi Riyanto Lampung Tengah - Muhammad Khoirul Huda; Fitriani; Durotun Nasikah (Universitas Muhammadiyah Metro, 2025)
Employee performance can decrease due to poor organizational culture, lack of motivation, and compensation mismatch with workload. This research aims to determine whether there is an influence of organizational culture, compensation and work motivation on employee performance at BMT Surya Abadi Riyanto, Central Lampung. The method used in research is quantitative. The population in the study was all 85 BMT Surya Abadi Riyanto Central Lampung employees. The sample used was 85 people using saturated sampling techniques. Data collection used a questionnaire method given by BMT Surya Abadi employees. Questionnaire scoring uses a Likert scale. The data analysis used in the research is multiple linear regression analysis, t-test, F test, and coefficient of determination. The research results show that there is a significant influence, both simultaneously and partially, between organizational culture, compensation and work motivation on employee performance. Thus it can be concluded that the higher or better the organizational culture, compensation provided, and motivation of employees, the higher the performance achieved by employees.